Isolation of specialized transducing bacteriophages carrying the structural genes of the hexuronate system in Escherichia coli K-12: exu region. - Mata, M (1978)
In Escherichia coli HfrH 58, isolated by Shimada et al., a heat-inducible phage has been integrated in a secondary attachment site. We have characterized tha nature of the lambda integration. The exuR regulatory gene is inactivated by prophage integration. Genetic and biochemical analysis indicated a gene order: uxaA-uxaC-exuT-(exuR')-lambdaNRAJ (exuR''). By induction of HfrH 58, one class of deletions extending into the exu region was obtained. Analysis of these deletions confirms the exu region topography and the regulatory mechanism of the hexuronate system previously described. It has been possible to regenerate a functional exuR gene by prophage exision. Various lambda transducing particles plaque-forming and defective transducing phages carrying the left part or the right part of the exu region, have been derived from the secondary site lysogen HfrH 58. A phage carrying the entire exuR region was constructed by a cross between these two types of phage. The construction and characterization of these exu transducing phages are presented.